(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
The starting point of the study is that andragogy has evolved into an important and subtle subsystem of pedagogy, education and public culture which can be and must be examined from a scientific point of view from several aspects and as a consequence, from a regional one as well. The aim of the study is to point to the presence, importance and development possibilities of research of regional approach in andragogy. According to this - in the first place in the scientific special literature of Hungary after the political restructuring and on the bases of different kinds of researches - it outlines the main directions of research of regional aspect, it analyses the interdisciplinary and inter-trade linking points in connection with it. It would like to give an answer if the ways of research and results could be an adequate basis for the emergence of a regional andragogy which can be defined as a special field within andragogy.